Taxonomic notes on the crab spider genus Oxytate L. Koch, 1878 (Araneae: Thomisidae) from India - Sudhin, Puthoor Pattammal; Sen, Souvik (Zootaxa, 2023)
Type specimens of poorly known Indian Oxytate species deposited in the National Zoological Collection, Zoological Survey of India, Kolkata, and the National Museum of Natural History (MNHN), Paris are re-examined and described. Oxytate subvirens (Strand, 1907) is recorded for the first time from India and the current distribution of the genus in India is also mapped.